Evaluation of Sexual Violence Victims: Cross-Sectional Research - Bork, Turgay; Tokgözlü, Ömer; Göçük, Vahap; Türkoglu, Abdurrahım (My University, 2022)
Objective: The present study was aimed to evaluate the \rcases presented with sexual abuse claims referred by judicial authorities for forensic examination. Material and Methods: The reports on \rcases presented to the Fırat University Faculty of Medicine Forensic \rMedicine Department Polyclinic with sexual abuse claims between \r2016 and 2020 were reviewed retrospectively. The cases were evaluated in terms of sociodemographic features and examination results. \rResults: Of the cases, 128 (82.6%) were female. 64.8% of the women \rpresented with vaginal penetration, and that the suspect was most frequently a friend or partner of the victim (38.2%), where 64 (41.3%) \rvictims applied within the first 3 days following the incident. Upon \rgenital examinations, the hymens in question were mostly in annular \rform (89.1%), 52.8% of the female cases were hymen injury, the natural notches were most frequently at the 3 and 9 o’clock locations \r(15.9%) in the lithotomy position, and that the tears were the most common at the 6 o’clock location (29.4%). 5.2% of all the cases had anal \rpenetration, and that 75% of the acute hymen tears and all the acute \ranal penetration were examination was found within first three days. \rConclusion: It is known that the detecting criminal manifestations becomes more challenging as the application is delayed following the sexual abuse incident. For this reason, we believe that it is important to \rdetermine the reasons for the delay in reporting the crime of the victims \rand to take the necessary precautions, in order to collect the findings of \rthe crime properly and to get the punishment they deserve.
Keywords: Adli Tıp